You need to substitute the numbers 1,2,...,10 for n, in equation `a_n = ((-1)^n)/(sqrt(n)), ` to list the first 10 terms of the sequence, such that:

`a_1 = ((-1)^1)/(sqrt1) => a_1 = -1`

`a_2 = ((-1)^2)/(sqrt(2)) => a_2 = 1/sqrt2`

`a_3 = ((-1)^3)/(sqrt(3)) => a_3 = -1/sqrt3`

Reasoning by analogy yields:

`a_4 = 1/sqrt4, a_5 = -1/sqrt5, a_6 = 1/sqrt6, a_7 = -1/sqrt7, a_8 = 1/sqrt8, a_9 = -1/sqrt9 = -1/3, a_10 = 1/sqrt10.`

**Hence, evaluating the first 10 terms of the sequence, using `a_n = ((-1)^n)/(sqrt(n)), ` yields `a_1 = -1, a_2 = 1/sqrt2, a_3 = -1/sqrt3,a_4 = 1/sqrt4, a_5 = -1/sqrt5, a_6 = 1/sqrt6, a_7 = -1/sqrt7, a_8 = 1/sqrt8, a_9 = -1/sqrt9 = -1/3, a_10 = 1/sqrt10. ` **